Implementasi Peraturan Bupati No. 5 Tahun 2005 Tentang Pembinaan dan Pengawasan Distribusi Tata Niaga Pengadaan dan Penyaluran Bahan Bakar Minyak di kecamatan Bengkalis Kabupaten Bengkalis - Effendi, Fenti; Sulistyaningsih, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Riau is a province that has twelve districts , namely Pekanbaru , Dumai , Bengkalis ,Rokan Hulu , Rokan Hilir , Indragiri Hulu , Indragiri Hilir , Kuansing , Kampar , Meranti Islands, Siak and Pelalawan the city thousands in Pekanbaru . Riau has some great potential Riau onerich in natural resources namely oil . As we know that one of the Riau oil producers in Indonesia.Precisely at Saber Duri subdistrict where the oil producers , which is one of the District who arein Bengkalis . In fact finite Bengkalis District to obtain fuel oil ( BBM ) .In theoretical models of implementation by Van Meter and Van Horn , there are sixvariables that shape the relationship between policies and performance , the basic measures andpolicy objectives , policy resources , inter- organizational communication and implementationactivities , the characteristics of the executing agency , economic conditions , social and political, as well as implementing tendencies .The method used in this research is qualitative research . With the technique that madethe snow ball sampling , the key informants in this study . In this paper that an informantresearch is Disperidag Bengkalis , APMS and Communities Agency . Then analyze the data andmanage .Based on the research that has been done , based on the theoretical concept . That theimplementation of Regulation No. Regents . 5 Year 2005 on Guidance and Control ofDistribution Business Administration Procurement and Distribution of Fuel Oil in BengkalisBengkalis district , has been implemented by the Department of Industry . But not maximum ,still there is a lack of fuel oil ( BBM ) in Bengkalis . Plus the lack of updates performed decree .Keywords : declaring , Development and Supervision , Implementation , Fuel Oil